The Very Best Daddy of All - Bauer, Marion Dane.; Elwell, Peter (New York : Simon & Schuster Books for Young Readers, 2004)
Pictures and rhyming text show how some fathers, animal, bird, and human, take care of their children by bringing them food, playing with them, and keeping them safe.
Keywords: Father and child -- Fiction; Animals -- Fiction; Stories in rhyme